EKSISTENSI PRAKTIK JUAL GADAI (ADOL SENDE) PADA MASYARAKAT DUSUN PENTONG KELURAHAN SELOREJO KECAMATAN PUNDHONG KABUPATEN BANTUL - Hidayah, Nur Putri; Rahadiyan, Inda (Faculty of Law, University of Muhammadiyah Malang, 2017)
Adol sende is a form of assurance that currently exists in rural and indigenous communities. Adol sende is implemented as an effort to fulfill people's life needs. But in practice, there is an extortion element in the implementation of adol sende because the object of guarantee is too long controlled by the creditor (controlled and used). This causes the debtor does not get the economic rights of the land which is used as the object of adol sende. In Article 7 of Act Number 56 Prp.1960 the government provides a limitation of the timing of adol sende implementation to overcome the extortion in farming practices. The purpose of this research is to know how to implement pawn transaction (adol sende) and constraints faced by people who live in Pentong Hamlet, Selorejo Subdistrict, Pundhong District, Bantul Regency in connection with the implementation of Article 7 of Law Number 56 Prp 1960. The research method is empirical sociology, research location is Pentong Hamlet, Selorejo Village, Pundhong District, Bantul Regency. The result of the research is the implementation of adol sende by the people of Pentong Hamlet, in relation to the implementation of Article 7 of Law Number 56 Prp 1960, there was no harmony. The Pentong community remains in their living law, where the implementation of adol sende is unlimited. The obstacles in the implementation of adol sende consists of 2 things, internal constraints because of ignorance of the community itself over the time limits set by the government. While external constraints exist in the absence of education in the form of socialization of the government against the provisions of Article 7 of Law Number 56 Prp 1960.